nona Conditioning Time Penambahan Nash Pada Flotasi Ore Stockpile Low Pyrite Dan High Pyrite Dengan Metode Control Potential Sulfidisation - nindi virginia nindi (Retii, 2019)
Amman Mineral Nusa Tenggara is one of the largest mining companies in Indonesia which processes copper ore into concentrates with associated minerals in the form of gold and silver. PT. Amman Mineral (PT. AMNT) processes rocks that have high levels in advance while for rocks that have low levels will be collected in the stockpile. The buildup of rocks in the stockpile causes an oxidation process in the ore rocks to be processed. The initial stage of processing using the Controlled potential sulphidisation flotation method is by taking samples and then sample preparation includes drying, comminution using jaw crusher and roll crusher, homogenization using coning & quartering, riffle and rotary splitter, and grinding using a rod mill. CPS flotation uses NaSH as a sulfidizing agent, which is a chemical that modifies the potential for sulfidization besides the chemicals used are dhitiophospate, potassium amylxanthate, frother (F583) and lime. At this research location, PT. AMNT can produce recovery from standard flotation which is lower than CPS and sulphide / oxide flotation, sulphide / oxide flotation with conditioning time variations. Keywords: Flotation, conditioning time, ore stockpile